Electrochemical characteristics of molten iron electrodes in slag and electrochemical properties of their interface. (1st September 2021) - Judge, W.D.; Paeng, J.; Azimi, G.
Highlights: Potential of zero charge shows metal side of double layer is positively charged at rest potential. Differential capacitance curves integrated for charge density and electrocapillary curves. Exchange current is 0.5 A cm –2 at 1600 °C with activation energy of 490 kJ mol –1 . Thickness of the diffusion layer in slag is 10–20 μm and grows as current flows. Abstract: Kinetic characteristics of molten iron/slag reactions and interfacial properties between molten iron/slag are of profound importance in steelmaking but quantitative electrochemical descriptions are lacking. Therefore, a detailed electrochemical investigation of pure (carbon-free) molten iron in slag was performed in the present work, using mostly impedance spectroscopy. Measurements were made between 1600–1700 °C at the rest potential and also at direct current biases to elucidate changes in interfacial properties when metal/slag reactions take place. Various fundamental physiochemical properties were measured for the first time including exchange currents, standard heterogeneous rate constants, Nernst diffusion layer thicknesses in slag, differential capacitance curves, potentials of zero charge, excess charge density curves, and electrocapillary curves. Results and discussion inform about the electric double layer formed between molten iron and slag. Graphical abstract: Image, graphical abstract